Prognostic Value of Histopathology and Trends in Cervical Cancer - Momina Khadija Abbasi, Nosheen Ali, Sehrish Naz, Ama Tul Naval, Mehak Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cervical cancer has an increased rate of morbidity and mortality among women most commonly in terms of cervical adenocarcinoma. Histopathology has been considered as the foundation for diagnosing the tissue changes associated with cervical cancer. However, there are controversies in identifying their prognostic value. Methods: It is a retrospective study in which 100 participants suffering from cervical adenocarcinoma and 200 participants of squamous cell carcinoma between the time period of 2017-2020 at the cancer center Pakistan were analyzed. The study was conducted between the time period of Dec, 2021 to Nov, 2022. All the patients were diagnosed histologically and were treated through radiotherapy or surgery. Demographic history along with area of registry, grade, size, stage and histology of tumor, diagnosis year, examination and involvement of lymph nodes, radiotherapy and type of surgery were assessed with the help of Akaike information criteria (AIC). Results: Total cancer records available for evaluation were 40,000 which were observed to be decreased from year after year from 2017-2020 but cases of squamous cell carcinoma and adenocarcinoma were observed to be increased with a rate of 100 patients per year. Their median age was recorded to be 52 years. Mortality associated with cause and without cause were dependent upon few variables including race, gender, diagnosis year, stage and grade of disease, ratio of nodes, size of tumor, radiotherapy and hysterectomy. Significance has been observed in the histological types (p = 0.003). Practical Implication: This study will be helpful for the oncologists, physicians and researchers in order to decide the best approach in terms of histopathology studies in the diagnosis of cervical cancer patients. It will help the community by carrying out a proper screening protocol for all the patients in order to prevent the patient from serious conditions. Conclusion: Study concluded that the chances of developing adenocarcinoma and squamous cell carcinoma are dependent upon the rate of poor survival. A large number of adenocarcinoma cases suggests that there is poor screening of the people reporting any signs and symptoms. Therefore, it is suggested to properly screen the women on a regular basis and specially those who report any of the symptoms associated with cervical cancer. Keywords: Cervical cancer, carcinoma, adenocarcinoma, squamous cell carcinoma, histopathology, histological types.